(untitled) (Bangladesh Journal of Otorhinolaryngology, 2013)
Castleman disease is a rare clinicopathological disorder associated with lymphoproliferation. We report the case of a 54 year old gentleman initially presenting with dysphagia followed by bilateral cervical lymphadenopathy, and later diagnosed as multicentric Castleman disease. To the best of our knowledge no case of Castleman disease presenting as dysphagia along with neck swelling has been previously described in the literature. This case report highlights a very unusual presentation of this rare disease. It also provides insight into the fact that because of the lack of any specific presenting symptoms and distinguishing radiographic features, an accurate histopathologic diagnosis and careful staging become crucial to planning treatment for this disease. DOI: http://dx.doi.org/10.3329/bjo.v19i1.12041 Bangladesh J Otorhinolaryngol 2013; 19(1): 53-57